2011
DOI: 10.1038/nphys2058
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected mass acquisition of Dirac fermions at the quantum phase transition of a topological insulator

Abstract: The three-dimensional (3D) topological insulator is a novel quantum state of matter where an insulating bulk hosts a linearly dispersing surface state, which can be viewed as a sea of massless Dirac fermions protected by the time-reversal symmetry (TRS). Breaking the TRS by a magnetic order leads to the opening of a gap in the surface state 1 , and consequently the Dirac fermions become massive. It has been proposed theoretically that such a mass acquisition is necessary to realize novel topological phenomena … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
261
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(272 citation statements)
references
References 21 publications
8
261
1
2
Order By: Relevance
“…115) The non-topological nature of TlBiS 2 naturally points to a topological phase transition, accompanied by a closing of the bulk band gap, occurring in the solid solution TlBi(S 1Àx Se x ) 2 . Such a transition was studied independently by Xu et al 116) and by Sato et al 117) and was found to be located at x ¼ 0:5. Intriguingly, Sato et al found an unexpected gap opening at the Dirac point when the composition is on the topological side and is close to the transition.…”
Section: Three-dimensional Tismentioning
confidence: 97%
See 1 more Smart Citation
“…115) The non-topological nature of TlBiS 2 naturally points to a topological phase transition, accompanied by a closing of the bulk band gap, occurring in the solid solution TlBi(S 1Àx Se x ) 2 . Such a transition was studied independently by Xu et al 116) and by Sato et al 117) and was found to be located at x ¼ 0:5. Intriguingly, Sato et al found an unexpected gap opening at the Dirac point when the composition is on the topological side and is close to the transition.…”
Section: Three-dimensional Tismentioning
confidence: 97%
“…Intriguingly, Sato et al found an unexpected gap opening at the Dirac point when the composition is on the topological side and is close to the transition. 117) This is surprising, because such a gap opening points to a lifting of the Kramers degeneracy, but in this system TRS is not explicitly broken. While the origin of this ''Dirac gap'' is not clear and its existence has been a matter of debate, a recent follow-up experiment substantiated its unique properties.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…By Eq. (14), 29 , where a gap of ∼ 10K can be achieved using microwave fields of intensity ≤ 1 W mm 2 . As opposed to the its 2D counterpart 10 , the surface modes emerging in the 3D driven system, allow direct probing of the driven topological state using a multitude of all-optical means.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent progress in the field of topological insulators has shown that stable 2D Dirac fermions exist ubiquitously on the surface of 3D topological insulators 1,2 . Moreover, through the careful studies on the topological phase transition between a 3D topological insulator and a normal insulator [4][5][6][7][8] , it is demonstrated that even the 3D Dirac fermions with the linear dispersion in all three momentum directions can be observed in the same material if we can reach the quantum critical point. As the 3D Dirac point (DP) with fourfold degeneracy does not carry a Chern number, the degeneracy at the gap-closing point can be easily lifted by small external perturbations, hence, the 3D Dirac fermions can be observed only at the single quantum critical point.…”
mentioning
confidence: 99%